PHENOMENOLOGICAL RELATIVISTIC STUDY OF THE ENERGY OF Α Λ IN ITS GROUND AND EXCITED STATES IN HYPERNUCLEI - Papadopoulos, G. J.; Koutroulos, C. G.; Grypeos, M. E. (HNPS Advances in Nuclear Physics, 2020)
The binding energy B_Λ of a Λ-particle in hypernuclei is studied by means of the Dirac equation containing attractive and repulsive potentials of orthogonal shapes. The energy eigenvalue equation in this case is obtained analytically for every bound state. An attempt is also made to investigate the possibility of deriving in particular cases approximate analytic expressions for B_Λ.